Knowledge, attitude and practice of family planning among married women of reproductive age in a VDC of eastern Nepal - Uprety, S; poudel, I S; Ghimire, A; Poudel, M; Bhattrai, S; Baral, D D (Journal of Chitwan Medical College, 2017)
Contraceptive use and fertility rates vary substantially among developing countries. An important factor, which affects the fertility of any population, is Contraceptive. Contraceptive use varies by age. Nepal over the past 15 years show an impressive increase in the use of modern contraceptive methods from 26 percent in 1996 to 43 percent in 2011. Objectives of the is to assess the knowledge, attitude regarding family planning and the practice of contraceptives among the married women of Dhabi VDC of Eastern Nepal. A descriptive cross-sectional observational study was done in Dhabi VDC. Total of 300 married women age 15-49 sample were taken from family planning center situated in Dhabi. Knowledge, attitude and practice on contraceptives were evaluated with the help of a predesigned questionnaire. Descriptive analysis was done by using SPSS 11.5 software to obtain frequencies and percentages. Out of 300 interviewed women, the mean age was 27.94 years, 98% had heard about Family planning method. Radio was the main Source of family planning information. Regarding the usage of contraceptive methods, about 79.3% had ever used and 63.3 had current using some sort of contraception, among the method used Injectables were the commonly used methods About 71% of married women other child in the further. Despite the knowledge of all family planning methods majority of the women used Injectables. Easily accessible and easily to use were the main reasons for choosing Injectables methods.